1990
DOI: 10.1267/ahc.23.427
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic bone formation in tumor stromal tissue. Immunohistochemical considerations.

Abstract: Ectopic and heterotopic bone formation rarely occur in stromal tissues of various epithelial tumors. In the present study, ectopic bone forming tumors; calcifying epithelioma Malherbe (6), renal cell carcinoma (1), thyroid adenocarcinoma (1) and ovary carcinoma (1) were examined. The process of ectopic bone formation could be classified into 1) bone formation related to epithelial tissue as found in calcifying epithelioma of Malherbe, 2) bone formation from perivascular smooth muscle, and 3) that due to metapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In canine benign mixed mammary tumours, transition of myoepithelial cells to cartilage has been documented by electron microscopical and histochemical studies examining chondroitin sulphuric acid and alkaline phosphatase (30,47,58). Transformation of modified myoepithelial cells has also been reported in humans (2,17,28,33) and the origin of pleomorphic adenoma of the breast from a single cell type capable of bidirectional differentiation has been suggested (14). However, our findings strongly suggest that cartilage and/or bone formation in canine mammary tumours results from stromal metaplasia, which is in line with histochemical studies concerning anionic heteroglycans (45).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…In canine benign mixed mammary tumours, transition of myoepithelial cells to cartilage has been documented by electron microscopical and histochemical studies examining chondroitin sulphuric acid and alkaline phosphatase (30,47,58). Transformation of modified myoepithelial cells has also been reported in humans (2,17,28,33) and the origin of pleomorphic adenoma of the breast from a single cell type capable of bidirectional differentiation has been suggested (14). However, our findings strongly suggest that cartilage and/or bone formation in canine mammary tumours results from stromal metaplasia, which is in line with histochemical studies concerning anionic heteroglycans (45).…”
Section: Methodssupporting
confidence: 90%
“…However, our findings strongly suggest that cartilage and/or bone formation in canine mammary tumours results from stromal metaplasia, which is in line with histochemical studies concerning anionic heteroglycans (45). This stromal metaplasia is a wellknown phenomenon in the stroma of epithelial tumours at different sites (33). In the canine fibroadenomas of the benign mixed type, a small number of cells positive for the basal cell keratins was found within the chondroid or osteoid matrix.…”
Section: Methodssupporting
confidence: 89%
“…10,17,18 BMPs are multifunctional proteins originally isolated from bone and are identified by their ability to induce ectopic cartilage and bone formation. 1,16 BMPs regulate various aspects of organogenesis during development 13,23 and osteogenesis. 24 These proteins also have been detected in various mesenchymal and epithelial tumors, and they participate in ectopic ossification or epithelial-mesenchymal interaction.…”
mentioning
confidence: 99%
“…24 These proteins also have been detected in various mesenchymal and epithelial tumors, and they participate in ectopic ossification or epithelial-mesenchymal interaction. 9,10,[16][17][18]29,34,35 It has been found that type IV collagen is important for the actions of BMPs because some types of BMPs, such as BMP-2 and BMP-7, can intimately bind to type IV collagen. 8,25 BMP-2 coexisting with type IV collagen induces psammoma bodies in human ovarian cancer.…”
mentioning
confidence: 99%
“…Thus, GAGs were found to occur specifically in the 1st stage of the BMP-implanted area. Fibrous or metaplastic ossification was reported to occur in connective tissue cells as seen in tumor stromal ossification (15,16,18,21) or experimental bone induction by urinary bladder transplantation (7,11). It is significant that BMP does not directly induce the replacement of bone tissues, but BMP directly induces the proliferation of neighboring undifferentiated mesenchyme cells, and these cells then induce chondroidal metaplasia.…”
Section: Discussionmentioning
confidence: 99%